Residents' Perceptions of Religious Tourism and its Socio- Economic Impacts on Host Communities: A Study of Redemption Camp, Mowe, Ogun State, Nigeria - Olukole, Titilayo Olufunke (The international journal of religious tourism and pilgrimage, 2022)
Religious tourism has been identified as one of the major tourism types with impacts on the sociocultural and economic life of the host community. Nigeria is well-known globally for high levels of Christian religious activities attracting worshippers from different countries. However, little is documented on the socio-economic impacts of the religious tourist flow to Christian religious sites on host communities in Nigeria. This paper was designed to investigate the socio-economic impact of Christian religious tourism on host communities, using the Redemption Camp, RCCG and Mowe Community, Lagos-Ibadan Expressway, Ogun State, Nigeria as a case study. Both quantitative and qualitative research methods were adopted and the research instruments used in the study were reconnaissance surveys and interviews involving informal as well as structured questionnaires. Findings reveal that the Redemption Camp has a vast array of modern infrastructure, financial and educational institutions, commercial, hospitality and recreational centres in addition to faith-related institutions. Religious tourism activities of the camp have advanced the way of life of the host community and positively impacted on their socio-economic development resulting in the creation of more job opportunities and the enhancement of Christian faith and improvement of the standard of living of the residents. However, respondents agreed that religious tourism has resulted in increased environmental pollution and traffic congestion of the host community. In conclusion, the study revealed that religious tourism activities in the area had tremendous positive socio-economic impacts with few challenges on the host community.